A Complementary Co−Ni Phosphide/Bimetallic Alloy‐Interspersed N‐Doped Graphene Electrocatalyst for Overall Alkaline Water Splitting. Issue 8 (12th February 2021) - Arunkumar, Paulraj; Gayathri, Sampath; Han, Jong Hun
Abstract: Echinops‐like bimetallic CoNiP−CoNi alloy is synthesized from a metal−organic framework (MOF) and serves as an efficient catalyst for the oxygen evolution reaction (OER), with a low overpotential of 300 mV in 1 M KOH at 10 mA cm −2 ( η 10 ). The cooperative effect of Ni and Co metal, as well as the interfacial properties of the integrated semiconducting phosphide/metallic alloy and electronic conductivity of the MOF‐derived carbon regulate the performance of the catalyst. Moreover, the bimetallic CoNiP/CoNi alloy catalyst is interspersed with N‐doped graphene, forming a triad catalyst that demonstrates superior activity towards the hydrogen evolution reaction ( η 10 =150 mV) and excellent durability, owing to interfacial effects of the triad catalyst, large electrochemical active surface area, and enhanced conductivity from N‐doped graphene. The stability of the carbon‐containing catalyst during OER (oxidation) is altered by the high reactivity of heteroatom dopant. The assembled CoNiP/CoNi/N−RGO||CoNiP/CoNi water electrolyzer delivers a reasonable cell potential of 1.76 V at 10 mA cm −2 . The synthesized bimetallic CoNiP/CoNi alloy‐based triad catalyst thus demonstrates excellent electrocatalytic activity and high durability suitable for efficient alkaline water splitting. Abstract : Triad catalyst : A triad catalyst incorporating a bimetallic CoNiP phosphide/CoNi alloy interface interspersed with N‐doped graphene demonstrates excellent bifunctional catalytic activity towards water splitting and excellent durability, owing to interfacial effects, a large electrochemical active surface area, and enhanced conductivity from N‐doped graphene.